A Review of Aviation Manufacturing and Supply Chain Processes - Samuel John Axtman; Joseph Wilck (International Journal of Supply Chain Management, 2015)
This paper provides an overview of modern aviation manufacturing and supply chain practices, including machining processes, 3D printing processes, and automation processes. Continuous improvement efforts in both manufacturing and supply chain practices are necessary for the industry to meet the increase in production demand of 35,000 aircraft over the next two decades.